2022-RA-1510-ESGO The protective role of conization before radical hysterectomy in cervical cancer. (20th October 2022) - Guijarro Campillo, Alberto Rafael; Sánchez-Romero, Javier; Rodríguez-Hernández, José Ramón; Cánovas, Laura; Barceló-Valcárcel, Francisco José; Nieto, Aníbal
Abstract : Introduction/Background: The risk of tumor spillage is associated with cervical mass size at the time of surgery, and some recent studies suggested that cervical conization may be a significant independent predictor of the risk of disease relapse. The purpose was stablish the impact of conization before radical histerectomy in early-stage cervical cancer. Methodology: A retrospective observational cohort study (n=91). 47 (51.7%) received preoperative cervical conization, 44 (48.3%) without preoperative cervical conization. Results: Perioperative complications were lower in the conization group (19 (40, 4%) vs 13 patients (29, 6%), p=0, 277). Relapses were higher in the non-conization group 23 (30.3%) vs 10 (17, 9%). DFS were higher in the conization group 81, 8% vs 62, 7% (HR 0.38, 95% CI 0.15 to 0.95, p=0.040). No differences in overall survival rate were reported between two groups (7, 1% vs 13, 2%, log-rank p = 0.685) (HR 0.71, 95% CI 0.16 to 3.10, p=0.646). Patients who underwent laparoscopy without prior conization had a 5.80 times higher chance of relapse compared with those who underwent a laparotomy with previous conization (HR 5.80, 95% CI 1.45 to 23.27, p=0.013). Patients who underwent laparoscopy with prior conization and those who underwent laparotomy without prior cone biopsy showed no differences in relapse rates compared with those who underwent laparotomy with prior conization (reference) (HR 2.14, 95% CI 0.50 to 9.24, p=0.306 and HR 2.07, 95% CI 0.52 to 8.27, p=0.305, respectively) Conclusion: We showed that patients with early-stage cervical cancer who underwent prior cervical conization followed by radical hysterectomy had a significantly lower risk of relapse with no differences in mortality rates.